6p+12=4p

Simple and best practice solution for 6p+12=4p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p+12=4p equation:


Simplifying
6p + 12 = 4p

Reorder the terms:
12 + 6p = 4p

Solving
12 + 6p = 4p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4p' to each side of the equation.
12 + 6p + -4p = 4p + -4p

Combine like terms: 6p + -4p = 2p
12 + 2p = 4p + -4p

Combine like terms: 4p + -4p = 0
12 + 2p = 0

Add '-12' to each side of the equation.
12 + -12 + 2p = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 2p = 0 + -12
2p = 0 + -12

Combine like terms: 0 + -12 = -12
2p = -12

Divide each side by '2'.
p = -6

Simplifying
p = -6

See similar equations:

| -4x+12=x+17 | | 12-9x=52-16x | | 3x-7=-4x | | 3x-7=-1 | | -x-6=-2 | | (x^2-9)(x+4)=0 | | 18+x=-2 | | X^4+6x=0 | | 5x-7=103 | | (x^2-2)(x^2+3)=0 | | 170-5x=6x+5 | | 5x+1=3x+13 | | -4x^2-4x+3=0 | | 6p+3=3p+12 | | q=4.5-0.5 | | P^2-6p+8= | | 5x-2=x-14 | | 58-5=8+19 | | 2(x-12)=3(x-8) | | -9x^2=100 | | 6x^2+486=0 | | 15+3x=-3 | | y+2=5y+18 | | y=-0.125+1.375+1.5 | | 108-5x=31x+20 | | 6h+5=4h-17 | | 2w-2x-y+7w+15x-5y= | | 124-3x=6x+16 | | 11x-3y+13w+3y-4w+2x= | | 6w+9y+5x+8x-15y+4w= | | 2a+3(a-7)=a+3 | | 4(2x-5)=3(8-x) |

Equations solver categories